Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Project Report : Community Health and Social Services Network (CHSSN) : Community Radio : January 1 to March 31, 2007 - Howarth, Kelly; Kueber, Russell (Community Health and Social Services Network (CHSSN), 2007)
The findings and processes were to be documented and shared with the Lower North Shore (local radio station and regional English-speaking organization, COASTERs Association). In addition, consultation and support was to be given to both service providers to increase their capacity to better serve the English-speaking regions in the future.

Global Development Plan : Strategy to Revitalize the English-language Minority Communities of Quebec : Sector Plans - Quebec Community Groups Network (QCGN) (2003)
The roots of the English-speaking community in Quebec go back nearly 250 years, and have a historic place in the development of the province. While English-speaking communities traditionally established their own institutions in the areas of religion, education and health and social services, that type of community engagement dissolved to a greater extent with the Quiet Revolution and the emergence of the modern Quebec state. Now, after 30 years of exodus and isolation, the time has come for the English-speaking community to become involved, to re-establish its presence in the policy and program decision-making areas that affect the daily lives of its members.